Cover Image. (16th July 2018) - Launonen, A.; Maikku, M.; Vuollo, V.; Pirttiniemi, P.; Valkama, A. M.; Heikkinen, T.; Kau, C. H.; Harila, V.
Abstract : The cover image, by Anniina Launonen et al., is based on the Original Article 3D follow‐up study of facial asymmetry after developmental dysplasia of the hip, DOI:10.1111/ocr.12230 .